Characterization of the corrosion influence on the fatigue behavior of intrinsic CFRP-steel-hybrids - Klein, M.; Hülsbusch, D.; Walther, F.; Bartsch, M.; Hausmann, J.; Frantz, M.; Lauter, C.; Tröster, Thomas

Efficient manufacturing of hybrid structures consisting of steel and CFRP with using residual heat / Effiziente Herstellung von Hybridbauteilen aus Stahl und CFK mithilfe von Restwärmeausnutzung - Frantz, M; Lauter, Christian; Tröster, Thomas; Hausmann, J.; Bartsch, M.; Hülsbusch, D; Walther, F.

Crash simulation of high strength automotive components using advanced failure models - Block, Holger; Marten, Thorsten; Tröster, Thomas

Quasistatic and crash tests of steel-CFRP hybrid pillar structures for automotive applications - Lauter, Christian; Niewel, Joerg; Tröster, Thomas (International Journal of Automotive Composites)

Entwicklung und Herstellung von Hybridbauteilen aus Metallen und Faserverbundkunststoffen für den Leichtbau im Automobil - Lauter, Christian

Crash performance of the new press hardenable steel 15MnB6 - Block, Holger; Marten, Thorsten; Weiß Borkowski, Nathalie; Tröster, Thomas

Numerical simulation of the energy absorption of fiber-reinforced plastics - Reuter, Corin; Flore, Dominik; Pöhler, Simon; Sauerland, Kim Henning; Tröster, Thomas

Selective-Laser-Melting materials under cyclic loading: Influence of process-inherent defects on the initiation and propagation of fatigue cracks - Leuders, S.; Riemer, A.; Richard, H. A.; Tröster, Thomas; Niendorf, T.

Evaluation of the effect of defects on the mechanical performance of components manufactured by selective laser melting - Leuders, S.; Tröster, Thomas; Brenne, F.; Riemer, A.; Richard, H. A.; Niendorf, T.

On the mechanical performance of structures manufactured by selective laser melting: Damage initiation and propagation - Leuders, S.; Tröster, Thomas; Riemer, A.; Richard, H. A.; Niendorf, T.

Reducing the power consumption of household refrigerators through the integration of latent heat storage elements in wire-and-tube condensers - Sonnenrein, G.; Elsner, A.; Baumhögger, Elmar; Morbach, A.; Fieback, K.; Vrabec, J. (International Journal of Refrigeration)

Apparatus for the measurement of the speed of sound of ammonia up to high temperatures and pressures - Dubberke, Frithjof H.; Rasche, David B.; Baumhögger, Elmar; Vrabec, Jadran (Review of Scientific Instruments)

Prediction methods for pool boiling heat transfer: A state-of-the-art review - Gorenflo, Dieter; Baumhögger, Elmar; Herres, Gerhard; Kotthoff, Stephan (International Journal of Refrigeration)

Autonomously driven railway cabin convoys — Communication, control design and experimentation - Henke, Christian; Trächtler, Ansgar (2013 International Conference on Connected Vehicles and Expo (ICCVE))

Effects of a mass finishing process on parts produced from Ultem 9085 by Fused Deposition Modeling - Fischer, M.; Schöppner, Volker (ANTEC)
Parts produced by Fused Deposition Modeling (FDM) tend to have rough and undulating surfaces with staircase effects on rounded and slanting areas of the part. This is due to the characteristics of the process. In many fields of application, high demands are made on the optical quality of the part. An improvement in the surface quality of FDM parts made of Ultem*9085 can be achieved through post-treatment with a mass finishing process. In this paper, FDM specimens are post-treated in a disk finishing unit. Influences of the mass finishing process are analyzed with regard to the dependence of surface quality on the various process parameters and on the finishing medium, grinding time and grinding speed. The finishing efficiency depends on the finishing media and decreases for lower finishing time. For all media a lower disk velocity results a smaller grinding effect, but there are clearly differences between the finishing media. The paper also discusses effects of the grinding process on the mechanical properties of the parts. Especially small part geometries and parts build in z-direction tend to break during the finishing process.

Mechanical Analysis of Lightweight Constructions manufactured with Fused Deposition Modeling - Bagsik, A.; Josupeit, S.; Schöppner, Volker; Klemp, E. (29th International Conference of the Polymer Processing Society)
Additive production techniques have the advantage of manufacturing parts without needing a forming tool. One of the most used additive manufacturing processes is "Fused Deposition Modeling" (FDM) which allows the production of prototypes and end-use parts. Due to the manufacture layer by layer, also complex part geometries can be created in one working step. Furthermore, lightweight parts with specific inner core structures can be manufactured in order to achieve good weightrelated strength properties. In this paper the mechanical behavior of lightweight parts manufactured with the 3D production system Fortus 400mc from Stratasys and the material Polyetherimide (PEI) with the trade name Ultem*9085 is analyzed. The test specimens were built up with different inner structures and building directions. Therefore, test specimens with known lightweight core geometries (e.g. corrugated and honeycomb cores) were designed. A four-point bending test was conducted to analyze the strength properties as well as the weight-related strength properties. Additionally the influence of the structure width, the structure wall thickness and the top layer thickness was analyzed using a honeycomb structure.

Tribologische Untersuchung eines neuen Werkzeughalters zur Polierbearbeitung von keramischen Fliesen - Sousa, F.J.P.; Glawe, M; Magyar, Balázs

Numerical Investigation of the Contact of Rough Surfaces - Magyar, Balázs; Sauer, B

Calculation of the efficiency of worm gear drives - Magyar, Balázs; Sauer, B

Simulation der Hysteresereibung von Elastomeren - Magyar, Balázs; Sauer, B